The Adeno-Associated Virus Type 2 Regulatory Proteins Rep78 and Rep68 Interact with the Transcriptional Coactivator PC4 - Weger, Stefan (American Society for Microbiology, 1999)
The adeno-associated virus type 2 (AAV-2) Rep78/Rep68 regulatory proteins are pleiotropic effectors of viral and cellular DNA replication, of cellular transformation by viral and cellular oncogenes, and of homologous and heterologous gene expression. To search for cellular proteins involved in mediating these functions, we used Rep68 as bait in the yeast two-hybrid system and identified the transcriptional coactivator PC4 as a Rep interaction partner. PC4 has been shown to mediate transcriptional activation by a variety of sequence-specific transcription factors in vitro. Rep amino acids 172 to 530 were sufficient and amino acids 172 to 224 were absolutely necessary for the interaction with PC4. The PC4 domains required for interaction were mapped to the C-terminal single-stranded DNA-binding domain of PC4. In glutathione S-transferase (GST) pull-down assays, in vitro-transcribed and -translated Rep78 or Rep68 proteins were bound specifically by GST-PC4 fusion proteins. Similarly, PC4 expressed in Escherichia coli was bound by GST-Rep fusion proteins, confirming the direct interaction between Rep and PC4 in vitro. Rep was found to have a higher affinity for the nonphosphorylated, transcriptionally active form of PC4 than for the phosphorylated, transcriptionally inactive form. The latter is predominant in nuclear extracts of HeLa or 293 cells. In the yeast system, but not in vitro, Rep-PC4 interaction was disrupted by a point mutation in the putative nucleotide-binding site of Rep68, suggesting that a stable interaction between Rep and PC4 in vivo is ATP dependent. This mutation has also been shown to impair Rep function in AAV-2 DNA replication and in inhibition of gene expression and inducible DNA amplification. Cytomegalovirus promoter-driven overexpression of PC4 led to transient accumulation of nonphosphorylated PC4 with concomitant downregulation of all three AAV-2 promoters in the absence of helper virus. In the presence of adenovirus, this effect was relieved. These results imply an involvement of the transcriptional coactivator PC4 in the regulation of AAV-2 gene expression in the absence of helper virus.